RAPID GROUPING OF MARINE PSYCHROTROPIC BACTERIA USING RESTRICTION FRAGMENT LENGTH POLYMORPHISM ANALYSIS OF PCR-AMPLIFIED 16S Rdna - Ocky Karna Radjasa; Hidetoshi Urakawa; Kumiko Kita-Tsukamoto; Kouichi Ohwada (JOURNAL OF COASTAL DEVELOPMENT, 1999)
Grouping of 78 psychrotrophic bacteria isolated from surface and deep-sea waters of the north-western Pacific Ocean was carried out by RFLP analysis on the basis of PCR-amplified 16S rDNA. Six RFLP patterns from surface water and eight RFLP patterns from deep-sea water were obtained by HhaI digestion. F pattern was only found in the surface water, while g, h, and I patterns exclusively exited in the deep-sea water. It was clearly shown that RFLP patterns of HhaI digestion were clear and distinguishable. This method is very simple and promises a rapid tool to group numerous isolated from natural environments.